Transformação dos resíduos resultantes da reciclagem energética de pneus automobilísticos em gesso - Pereira, Ana Luiza Costa (2016)
The world industrial production system generates a lot of waste, which is largely released into the environment. However, much of this waste could be reused or recovered. This is the case of the tire industry applied to motor vehicles. Many tires are also improperly disposed or, when disposed in ecopoints, they quickly fill places due to size, low compression ratio and slow degradation. The incineration of this material is still an alternative; however, if held outdoors, it causes pollution in the air, soil and water, in addition to causing health problems to the population. The gas cleaning filter allows this burning to be performed without causing damage to the environment. The wastewater produced by gas cleaning has an acidic pH due to the presence of sulfur and other compounds. Therefore, this study assessed the efficiency of a gas cleaning filter used in the combustion of scrap tires and wastewater neutralization, by the addition of calcium carbonate. It was found that the filter retained sulfur at values of 3000 mg/L, succeeding, since there was no sulfur dioxide emission. When the wastewater was neutralized with calcium carbonate, calcium sulfate (CaSO4) was formed. The water spray also retained heavy metals (Cr, Cd, Pb, As) during burning.